PENGARUH FASILITAS BELAJAR TERHADAP MOTIVASI DAN HASIL BELAJAR FISIKA MAHASISWA - Andi Reski (Musamus Journal of Science Education, 2018)
This study is an "expost-facto" study which aims to analyze the influence of: (1) learning facilities on physics learning results of students; (2) learning facilities on learning motivation of students at; and (3) ) learning motivation on physics learning results of students. The population in this study were all students of class 2015 and class of 2016 Study Program of Physics Education at with a total of 224 people. The research sample was taken using the Slovin technique with a total of 145 students. The data collection process was carried out using questionnaires and tests of physics learning outcomes that have been empirically tested. The results of the research data were analyzed using Structural Equation Modeling analysis method with Analysis of Moment Structures technique. Through this model it can be concluded: (1) learning facilities have a positive direct influence on students learning motivation at; (2) learning facilities do not have a positive direct influence on the results of students studying physics at; and (3) learning motivation has a positive direct influence on the results of students learning physics.